Genetic diversity analysis and core collection construction of tea plant from the Yunnan Province of China using ddRAD sequencing - Weihua Sun; Chunlin Chen; Linlin Xu; Lingling Tao; Xiaoyan Tong; Yiping Tian; Huibing Jiang; Linbo Chen; Huilin Wen; Shengrui Liu; Chaoling Wei; Junyan Zhu (BMC Plant Biology)
Abstract Tea plants are economically important woody plants that originated in southwestern China. The Yunnan Province in China is regarded as the central origin of tea plants owing to the abundance and diversity of the tea germplasm present in this region. However, there is a lack of knowledge regarding the genetic diversity and evolutionary relationships among tea plants in this region. Here, a total of 266,397 high-quality single nucleotide polymorphisms were obtained using double digest restriction-site associated DNA sequencing from 468 tea accessions collected from Yunnan. The phylogenetic relationship and population structure of the 468 tea accessions revealed remarkable inter- and intraspecific introgression across different sect. Thea species. We found that Camellia taliensis (W. W. Smith) Melchior is the main genetic donor that greatly contributed to the domestication of C. sinensis (L.) O. Kuntze, as evidenced by the frequent generation of genetic intermediates derived from the hybridization between C. sinensis and C. taliensis in Lincang, Xishuangbanna, and Pu’er. Notable genetic differences were observed across the populations from distinct regions of Yunnan. Additionally, the Lancang River may have attenuated the genetic interflow between Lincang and Pu’er. Finally, a core collection of 50 tea accessions was constructed based on the genetic diversity of the 468 tea accessions. Our results provide novel insights into the evolutionary and domestication history of tea plants in Yunnan Province and can facilitate the development of strategies for the conservation, breeding, and utilization of the core collection.